MALAQBIQ LOCAL VALUE IN EFL WRITING CLASS - Rabiatul Adawiah; Prisna Aswarita Putri (Elite : English and Literature Journal, 2021)
The purpose of this study is to integrate malaqbiq local value, Islamic values, and language skill in Writing in General Communication course. It was conducted at English Education study program of STAIN Majene in 2019 by employing descriptive qualitative research method with total of 32 participants. Data gathered from interview, field notes, questionnaire, and RPS document analysis showed that the process of implementing malaqbiq value which included planning, implementation, and evaluation of learning had not encountered such a big obstacle because it has been supported by vison-mission of STAIN Majene which exemplify the value per se and the learning achievements of KKNI curriculum which contains affective aspect. Indicators of malaqbiq value related to writing skill are having a broad and advanced view in writing; creating introductory paragraphs/statements containing greetings; choosing appropriate diction according to context; composing words appropriately according to grammar; using proper spelling of words; writing correct information; writing with sense of relief (based on personal judgement); writing with authenticity and one own’s ideas (no plagiarism); writing with regards to context (who and where); and writing text according to rules.